Injuries in high-performance fencers - a review - Swatowska, M.; Akbas, A.; Juras, G. (Archives of Budo, 2020)
Background and Study Aim: Competitive fencing is a demanding sport with a long history and a promising future. Fencing is very dynamic sport that exposes practitioners to injury. The cognitive purpose of this study was review the prevailing type and location of injuries, basic on the following criteria: how high the incidence rates of the resulting damages is, and what are the risk factors, such as gender or weapon.